EMERGING THREAT OF NECROTIC ENTERITIS IN POULTRY AND ITS CONTROL WITHOUT USE OF ANTIBIOTICS: A REVIEW - S. A. Abid; T. Azeem; Z. I. Chaudhary; Mansur-ud-din Ahmad2 Z. U. Rehman; S. Umar3 (Journal of Animal and Plant Sciences, 2016)
Necrotic enteritis (NE) is an emerging economically significant problem of poultry caused by a bacterium Clostridium perfringens. The rising incidence of Clostridium infections and development of NE in commercial chickens has been associated with the withdrawal of antibiotics. There is an urgent need to control NE after European ban on the use of antibiotics as growth promoters in animal feed. Prevention strategies include avoiding predisposing factors, such as coccidiosis, and in-feed supplementation with a variety of feed additives. Supplementation of poultry diet with pre and probiotics has proven to be efficient to increase broiler chickens performance (health, weight gain, feed conversion) and to prevent or reduce the incidence of diseases caused by pathogenic bacteria. However, vaccination with modified toxin or other secreted immunogenic proteins seems a logical preventive tool for protection against a toxin-producing bacterium. This review describes the recent developments in novel preventive treatments againstC. perfringens induced NE and highlights the role of pre and probiotics, bacteriophages and vaccine for the better control of NE.
Keywords: Necrotic enteritis; Clostridium perfringens; Pathogenesis; Control measures